2022
DOI: 10.1039/d1sc06634j
|View full text |Cite
|
Sign up to set email alerts
|

Temperature triggered alternating copolymerization of epoxides and lactones via pre-sequenced spiroorthoester intermediates

Abstract: We report the alternating copolymerization of caprolactone and epoxide through the in situ formation of pre-sequenced spiroorthoester monomer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…[97] Very recently, the Mehrkhodavandi group developed an alternating copolymerization of ɛ-caprolactone and 1,2-epoxy-7-octene to form poly(ester-alt-ethers) mediated by a cationic In III complex (Scheme 4d). [106] The copolymerization involved the in situ formation of spiro-orthoester between CL and epoxide at 60 °C, followed by subsequent ROP of spiro-orthoester at 110 °C to form alternating copolymers with M n s up to 44 kDa and Đs ~1.2-1.4.…”
Section: Lactone/epoxidementioning
confidence: 99%
“…[97] Very recently, the Mehrkhodavandi group developed an alternating copolymerization of ɛ-caprolactone and 1,2-epoxy-7-octene to form poly(ester-alt-ethers) mediated by a cationic In III complex (Scheme 4d). [106] The copolymerization involved the in situ formation of spiro-orthoester between CL and epoxide at 60 °C, followed by subsequent ROP of spiro-orthoester at 110 °C to form alternating copolymers with M n s up to 44 kDa and Đs ~1.2-1.4.…”
Section: Lactone/epoxidementioning
confidence: 99%
“…In our work with cationic indium catalysts, , we have shown that their stability and reactivity can be significantly influenced by the addition of a hemilabile donor arm to the ligand backbone. , For example, adding a furfuryl pendant arm to A results in a catalyst with controlled activity and a long shelf life . Herein, we elucidate the mechanism of spiro-orthoester formation using cationic indium complexes with hemilabile furfuryl pendant arms.…”
Section: Introductionmentioning
confidence: 99%
“…26 Subsequently, we reported that A is capable of catalyzing the temperature-triggered double ring-opening polymerization of spiro-orthoesters to yield alternating poly(ether-alt-esters) with the highest molecular weights reported to date (>40,000 g/ mol). 27 In our work with cationic indium catalysts, 27,28 we have shown that their stability and reactivity can be significantly influenced by the addition of a hemilabile donor arm to the ligand backbone. 29,30 For example, adding a furfuryl pendant arm to A results in a catalyst with controlled activity and a long shelf life.…”
Section: ■ Introductionmentioning
confidence: 99%
“…17−26 Recently, we have shown that alkylindium complexes are unique catalysts for polymerization, 27,28 selective coupling of epoxides and lactones, 29 and the controlled polymerization of the resulting presequenced monomers to form perfectly alternating copolymers. 30 In trying to understand the reason for the reactivity patterns that we observed with these systems, our ability to study the relative Lewis acidity and mechanisms was frustrated by the variability added with each new ancillary ligand. We hypothesized that simpler, solvent-stabilized dialkyl cations, such as those reported by Neumuller (A), 17 Atwood (B, C), 18,19 Brintzinger (D), 20 Klosin and Chen (E, F), 21 Okuda (G, H, I), 22−24 Reed (J), 25 and Knapp (K), 26 could potentially act as easily accessible platforms for comparing the Lewis acidity and reactivity of cationic gallium and indium complexes (Chart 1).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently, we have shown that alkylindium complexes are unique catalysts for polymerization, , selective coupling of epoxides and lactones, and the controlled polymerization of the resulting presequenced monomers to form perfectly alternating copolymers . In trying to understand the reason for the reactivity patterns that we observed with these systems, our ability to study the relative Lewis acidity and mechanisms was frustrated by the variability added with each new ancillary ligand.…”
Section: Introductionmentioning
confidence: 99%